Clarifying the Scope of Conceptual Transfer. Issue 3 (2nd November 2015) - Jarvis, Scott
Abstract : This article clarifies the purposes of research on conceptual transfer by defining it as cross‐linguistic influence in the expression and interpretation of conceptual meaning and by discussing what conceptual meaning entails and how conceptual meaning and conceptual transfer relate to the pursuits of linguistic relativity research, on the one hand, and traditional research on cross‐linguistic influence on the other. I focus on three general questions that span the scope of conceptual transfer research, and I discuss the types of empirical evidence they call for. I also explore a case of meaning‐related transfer whose specific causes have not yet been identified, and I describe how a combination of types of evidence can be used to determine whether learners from different language backgrounds rely on different conceptual considerations when deciding how to refer to a particular spatial relationship. The article concludes with a summary of the purposes and importance of this line of inquiry.